2021
DOI: 10.3390/pathogens10080997
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response and Apoptosis-Related Pathways Induced by Aeromonas schubertii Infection of Hybrid Snakehead (Channa maculata♀ × Channa argus♂)

Abstract: Aeromonas schubertii is the etiological pathogen of internal organ nodules in snakehead fish. Infections with A. schubertii produce a significant economic loss in aquaculture. Therefore, it is important to examine the immune mechanisms by which snakeheads defend against A. schubertii infection. In this study, we established a hybrid snakehead infection model by intraperitoneal injection of A. schubertii that produced internal organ nodules. The splenic immune response of infected fish was examined at the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…schubertii at the transcriptome level by Illumina-seq analysis and found that A. schubertii activated a variety of innate immune cytokines involved in immune regulation (Liu et al, 2021). We found that C-13326 peptide significantly down-regulated pro-inflammatory cytokine IL1, IL8, IL12 and TNFα in spleen of hybrid snakehead infected with A. schubertii.…”
Section: The Extremely Low Concentrations Of Amps In Organisms Meansmentioning
confidence: 80%
See 1 more Smart Citation
“…schubertii at the transcriptome level by Illumina-seq analysis and found that A. schubertii activated a variety of innate immune cytokines involved in immune regulation (Liu et al, 2021). We found that C-13326 peptide significantly down-regulated pro-inflammatory cytokine IL1, IL8, IL12 and TNFα in spleen of hybrid snakehead infected with A. schubertii.…”
Section: The Extremely Low Concentrations Of Amps In Organisms Meansmentioning
confidence: 80%
“…Certain cytokine genes have been linked to the innate immune response, which of them are known to be important in protecting against pathogenic microorganisms in various fish species. A previous study has been conducted the spleen immune response of hybrid snakehead infected with A. schubertii at the transcriptome level by Illumina‐seq analysis and found that A. schubertii activated a variety of innate immune cytokines involved in immune regulation (Liu et al., 2021). We found that C‐13326 peptide significantly down‐regulated pro‐inflammatory cytokine IL1 , IL8 , IL12 and TNF‐α in spleen of hybrid snakehead infected with A. schubertii .…”
Section: Discussionmentioning
confidence: 99%
“…Of all the organs inspected, the spleen had one of the worst injuries. Numerous researchers have noticed bacterial infection-induced cellular degeneration in the spleen (Mawdesley-Thomas, 1969;Ferguson & McCarthy, 1978;Huizinga et al, 1979;Liu et al, 2021). Wolke (1975) thought that severe hematopoietic and structural connective tissue necrosis of the spleen was the most prominent lesion.…”
Section: Histopathological Index Of Spleenmentioning
confidence: 99%
“…Since hematopoiesis is one of the functions of the spleen (Grizzle & Rogers, 1976), injury or damage to the spleen could cause the inability to produce erythrocytes and leucocytes resulting in anemia and leucopenia. Histopathology of the liver, kidney, and spleen of naturally infected fish was validated with severe pathologies such as macrophage aggregation with hepatitis, degeneration of hematopoietic tissues, and granulomatous splenitis (Loch et al, 2017;Mamun et al, 2022). This was consistent with clinical manifestations of fish, including reduced response and appetite or stopped eating.…”
Section: Histopathological Index Of Spleenmentioning
confidence: 99%
“…In addition, Latif‐Eugenín et al (2016) documented three isolates of A. schubertii isolated from mussels, which carried the aerA and lafA virulence genes and showed susceptibility to all antibiotics tested. In aquaculture, A. schubertii was identified as an emergent disease in aquaculture (e.g., Cao et al, 2021; Latif‐Eugenín et al, 2016; Liu et al, 2021; Talagrand‐Reboul et al, 2020). Thus, antibiotic therapies have been routinely used to manage this fish disease.…”
Section: Introductionmentioning
confidence: 99%